2012
DOI: 10.1038/nmeth.2185
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic device and computational platform for high-throughput live imaging of gene expression

Abstract: To fully describe gene expression dynamics requires the ability to quantitatively capture expression in individual cells over time. Automated systems for acquiring and analyzing real-time images are needed to obtain unbiased data across many samples and conditions. We developed a microfluidics device, the RootArray, in which 64 Arabidopsis thaliana seedlings can be grown and their roots imaged by confocal microscopy over several days without manual intervention. To achieve high throughput, we decoupled acquisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
95
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 31 publications
0
95
0
Order By: Relevance
“…Although microfluidic devices have been used to study different aspects of plant cell biology such as gene expression (Busch et al, 2012), cell biomechanics (Sanati Nezhad et al, 2013a, b), cellular mechanism of growth (Agudelo et al, 2013;Grossmann et al, 2011;Sanati Nezhad et al, 2014), phenotyping of plant organs (Jiang et al, 2014), and chemical stimulation of plant cells (Sanati Nezhad et al, 2013c), they had not been performed adequately enough with walled plant cells, so far. The reason is that these cells are not attached to a surface as mammalian cells, but have to be cultivated in suspension.…”
Section: Introductionmentioning
confidence: 99%
“…Although microfluidic devices have been used to study different aspects of plant cell biology such as gene expression (Busch et al, 2012), cell biomechanics (Sanati Nezhad et al, 2013a, b), cellular mechanism of growth (Agudelo et al, 2013;Grossmann et al, 2011;Sanati Nezhad et al, 2014), phenotyping of plant organs (Jiang et al, 2014), and chemical stimulation of plant cells (Sanati Nezhad et al, 2013c), they had not been performed adequately enough with walled plant cells, so far. The reason is that these cells are not attached to a surface as mammalian cells, but have to be cultivated in suspension.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the methods implementing continuous cell tracking have a promising potential to overcome the complexity of investigation of tissue growth and hemostasis at the cellular level [222]. Analysis of cell tracking within microfluidic devices which provide a real time monitoring of biological samples in a controllable condition is a desirable achievement that can reveal the extensive unknown factors in tissue development studies [223,224]. However, these techniques are not applicable without implementing computational and statistical analyses to process large data obtained from monitoring the samples [225].…”
Section: Methodsmentioning
confidence: 99%
“…Physiological growing conditions in the microscope specimen chamber are crucial for long-term experiments. There are a number of protocols available that describe imaging growth chambers for confocal microscopes [1][2][3] . However, confocal microscopy introduces high light-intensity to the plant, which can cause stress responses and usually inhibits the growth 4 .…”
Section: Introductionmentioning
confidence: 99%